Among psychedelic-experienced users, only past use of psilocybin reliably predicts nature relatedness. (January 2023) - Forstmann, Matthias; Kettner, Hannes S; Sagioglou, Christina; Irvine, Alexander; Gandy, Sam; Carhart-Harris, Robin L; Luke, David
Background: Past research reports a positive relationship between experience with classic serotonergic psychedelics and nature relatedness (NR). However, these studies typically do not distinguish between different psychedelic compounds, which have a unique psychopharmacology and may be used in specific contexts and with different intentions. Likewise, it is not clear whether these findings can be attributed to substance use per se or unrelated variables that differentiate psychedelic users from nonusers. Aims: The present study was designed to determine the relative degree to which lifetime experience with different psychedelic substances is predictive of self-reported NR among psychedelic-experienced users. Methods: We conducted a combined reanalysis of five independent datasets ( N = 3817). Using standard and regularized regression analyses, we tested the relationship between degree of experience with various psychedelic substances (binary and continuous) and NR, both within a subsample of psychedelic-experienced participants as well as the complete sample including psychedelic-naïve participants. Results/Outcomes: Among people experienced with psychedelics, only past use of psilocybin (versus LSD, mescaline, Salvia divinorum, ketamine, and ibogaine) was a reliable predictor of NR and its subdimensions. Weaker, less reliable results were obtained for the pharmacologically similar N, N -dimethyltryptamine (DMT). Results replicate when including psychedelic-naïve participants. In addition, among people exclusively experience with psilocybin, use frequency positively predicted NR. Conclusions/Interpretation: Results suggest that experience with psilocybin is the only reliable (and strongest) predictor of NR. Future research should focus on psilocybin when investigating effects of psychedelic on NR and determine whether pharmacological attributes or differences in user expectations/use settings are responsible for this observation.